Strengthening initiatives in urban farming and food security through a mixed-use Urban Agriculture Center in Quezon City - Rayel, Jasmine R. (College of Architecture, University of the Philippines Diliman, 2022)
In 2015, the Philippines was listed as the number one most affected country by climate change in the Global Climate Risk Index. The effects of climate change such as the increase in rainfall, droughts, and flooding are greatly felt in the agriculture sector because it disrupts crop productivity and distribution, therefore threatens the food security of the country. This gives urban areas a disadvantage because they heavily rely on the distribution of agricultural products from agricultural regions. With the disruption of climate change in agriculture and the rapid rise of population in urban areas, the need for sustainable action with regards to food system is important to prevent food insecurity. this thesis explores ways to address food insecurity in urban areas by promoting urban farming. Since there are limited agricultural lands in the cities and continuous soil degradation, the need for modern farming techniques is needed. Despommier, a microbiologist and ecologist introduced vertical farming, an indoor farming innovation that can help meet the challenges of the growing urban population. By integrating food production into city living, it gears toward an urban life sustainability where food security can be attained. Although vertical farming has many benefits, it also has challenges which need to be addressed. Since this thesis focuses on urban food security, the chosen site for this thesis is in Quezon City, a highly urbanized city in Metro Manila where it accounts as the city with the highest population in the Philippines. Quezon City started its initiatives towards the implementation of urban farming and this thesis aims to strengthen the initiatives of the city through architectural intervention in the form of an Urban Agriculture Center. The center will be integrated with livelihood opportunities, research and development, education and farming and food processing training, feeding programs, commercial areas, and recreation to further develop the agenda of strengthening food security and urban farming in the cities in a more sustainable way.